La loi du 3 janvier 1979 et les archives privées - Bonazzi, Chantal (Gazette des archives, 1979)
The Archives Law of 3 January 1979 and private archives. Access to private archives, when they are deposited in a Public Archive repository, is subject to conditions stipulated by the deposer. Several solutions can be recommended. Private archives remaining in the custody of their owners can be protected by a decision of " classification which makes abusive exportation impossible. The author stresses the importance of modem (contemporary) private archives.